PENANAMAN ETIKA KOMUNIKASI BISRI MUSTOFA DALAM PROSES PEMBELAJARAN DI MA NURUL ISLAM BOYOLALI - Wahid Tuftazani Rizqi (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This study aims to explore Bisri Mustofa's conception of the ethics of community communication and its application in MA Nurul Islam Boyolali. This research is a qualitative field research with a case study approach. The paradigm used is constructivism-interpretive paradigm. The data analysis technique goes through three stages, namely data reduction, data presentation, and drawing conclusions. The concept used in this research is the learning concept of Bisri Mustofa. The results conclude that: Bisri Mustofa's conception in education is to pay special attention to how to convey information to others in good language, and the absence of one's feelings in communicating. This conception can be instilled in the community through education by paying attention to learning, learning methods, and evaluating learning objectives. In its application, Madrasah Aliyah Nurul Islam Boyolali seeks to apply this conception by paying attention to the learning implementation plan and also the learning process.